The Impact of Intra-Arterial Papaverine-Hydrochloride on Cerebral Metabolism and Oxygenation for Treatment of Delayed-Onset Post-Subarachnoid Hemorrhage Vasospasm. Issue 4 (3rd December 2019) - Hosmann, Arthur; Wang, Wei-te; Dodier, Philippe; Bavinzski, Gerhard; Engel, Adrian; Herta, Johannes; Plöchl, Walter; Reinprecht, Andrea; Gruber, Andreas
Abstract: BACKGROUND: Delayed posthemorrhagic vasospasm remains among the major complications after aneurysmal subarachnoid hemorrhage (SAH) and can result in devastating ischemic strokes. As rescue therapy, neurointerventional procedures are used for selective vasodilatation. OBJECTIVE: To investigate the effects of intra-arterial papaverine-hydrochloride on cerebral metabolism and oxygenation. METHODS: A total of 10 consecutive patients, suffering from severe aneurysmal SAH were prospectively included. Patients were under continuous multimodality neuromonitoring and required intra-arterial papaverine-hydrochloride for vasospasm unresponsive to hypertensive therapy. Cerebral metabolism (microdialysis), brain tissue oxygen tension (ptiO2), intracranial pressure (ICP), and cerebral perfusion pressure (CPP) were analyzed for a period of 12 h following intervention. RESULTS: A median dose of 125 mg papaverine-hydrochloride was administered ipsilateral to the multimodality probe. Angiographic improvement of cerebral vasospasm was observed in 80% of patients. During intervention, a significant elevation of ICP (13.7 ± 5.2 mmHg) and the lactate-pyruvate ratio (LPR) (54.2 ± 15.5) was observed, whereas a decrease in cerebral glucose (0.9 ± 0.5 mmol/L) occurred. Within an hour, an increase of cerebral lactate (5.0 ± 2.0 mmol/L) and glycerol (104.4 ± 89.8 μmol/L) as well as a decrease of glucose (0.9 ± 0.4 mmol/L) were measured. In 2 to 5 h after treatment, the LPR significantly decreased (pretreatment: 39.3 ± 15.3, to lowest 30.5 ± 6.7). Cerebral pyruvate levels increased in 1 to 10 h (pretreatment: 100.1 ± 33.1 μmol/L, to highest 141.4 ± 33.7 μmol/L) after intervention. No significant changes in ptiO2 or CPP occurred. CONCLUSION: The initial detrimental effects of the endovascular procedure itself were outweighed by an improved cerebral metabolism within 10 h thereafter. As the effect was very limited, repeated interventions or continuous application should be considered.